The Effectiveness of Clinical Supervision in Developing Teachers’ Professional Competence: A Quantitative Study at SD Negeri 1 Kalipang Rembang - Lailiyah, Muhimatul; Haryati, Titik; Sumarno, Sumarno (Journal of Educational Sciences, 2025)
Teacher professional competence is a key determinant of education quality, yet many schools struggle to meet established competency standards. At SD Negeri 1 Kalipang, Rembang, aspects such as lesson planning, teaching strategies, and classroom management remain below expected benchmarks. This study aims to examine the effectiveness of clinical supervision in enhancing teachers’ professional competence. Using a qualitative case study approach, data were gathered through in-depth interviews, classroom observations, and document analysis involving the principal and selected teachers. The supervision process was implemented in three structured stages: pre-observation meeting, classroom observation, and post-observation reflection. Findings reveal that clinical supervision, when applied in a dialogic, collaborative, and supportive manner, significantly improved teachers’ instructional planning, pedagogical strategies, and classroom management. Teachers reported increased motivation, stronger professional responsibility, and enhanced reflective practice through constructive feedback and collegial dialogue. Moreover, the process fostered a culture of continuous learning and peer collaboration within the school. The study concludes that clinical supervision serves not only as a developmental tool but also as a catalyst for sustainable professional growth, contingent on effective leadership and institutional commitment.